Modeling of Tire Lateral Forces in Non-linear 6-DOF Simulations for Off-Road Vehicles. Issue 32 (2022) - Badar, Tabish; Backman, Juha; Visala, Arto
Abstract: This study highlights the use of a linear model to generate lateral forces in a nonlinear vehicle driving simulation. The crucial thing about modeling lateral forces is the centripetal acceleration limit a ground vehicle may experience. One can employ a linear model to simulate lateral forces when the commanded lateral acceleration for an off-road car-like vehicle (such as Polaris - an electric all-terrain vehicle) is limited to 3 m/s 2, and for a heavy forest truck (for example, Ponsse's Bison - a forwarder) to about 1 m/s 2 . Tire construction, which plays a significant role in the load-carrying capability and the cornering of a ground vehicle, is considered in this paper. An estimate of the cornering stiffness for the tires is determined using Hewson's model, which uses only the basic information mentioned in their datasheets. At the maximum rated load, a cornering stiffness coefficient value is obtained. The cornering coefficient is used to simulate lateral forces as the function of vertical load and sideslip angle. The simulation results highlight the advantages and deficiencies of using a linear tire model to generate lateral forces for off-road vehicles. Finally, the simulation data is analyzed, where the results are compared with those obtained from a standard kinematic model.